Simulation of Jet Drying of a Moist Cylinder at Low Reynolds Number - Alnak, D. Engin; Varol, Yasin; Öztop, Hakan Fehmi; Al-Salem, Khaled (Taylor & Francis Inc, 2012)
A numerical analysis of the process of jet drying of a moist cylinder was conducted. The drying jet was a laminar 2D jet stationed at three different distances (D/H = 0.22, 0.25, and 0.33) from the moist cylinder to investigate the jet effectiveness on heat and mass transfer. The diameter of the object and initial jet height were fixed in all cases. Temperature and mass distributions were obtained inside the object for different jet velocities. A finite volume method was used to solve the governing equations for momentum and energy with a commercial code. Calculations were performed for three different Reynolds numbers, namely, Re = 100, 200, and 300. It was found that heat and mass transfer increased with decreasing the distance, D/H, between the jet and the cylinder. In addition, increasing Reynolds number showed a positive effect on heat and mass transfer. Locally, jet drying was found to be most effective near the stagnation point on the leading side of the cylinder.
Keywords: Drying; Fluid flow; Jet impingement; Mass transfer